Coming Out to Dad: Young Gay and Bisexual Men's Experiences Disclosing Same-Sex Attraction to Their Fathers. (July 2015) - Jadwin-Cakmak, Laura A.; Pingel, Emily S.; Harper, Gary W.; Bauermeister, José A.
Few studies have examined the relationship between young gay and bisexual men (YGBM) and their fathers. Based on a phenomenological framework, this study investigated the role of fathers in YGBM's coming-out experience, focusing on how fathers responded to disclosure of same-sex attraction, how fathers' responses compared with sons' expectations, and what sons perceived as having influenced their fathers' responses. Semistructured in-depth interviews with 30 gay and bisexual men aged 18 to 24 years were conducted as part of a larger study; topics explored in the interview included experiences coming out to family and others. Nineteen participants' narratives included discussion about their fathers and were included in the current analyses. The YGBM who were interviewed perceived a complex range of responses upon coming out to their fathers, ranging from enthusiastic acceptance to physical violence. Participants spoke of fathers who were accepting in different manners and who often held contradictory attitudes about same-sex attraction. Fathers' responses commonly differed from sons' expectations, which were informed by homophobic talk and gendered expectations. Sons spoke about what informed their expectations as well as what they perceived as influencing their fathers' responses, including gender norms, beliefs regarding the cause of same-sex attraction, religious and sociopolitical views, and concerns about HIV/AIDS. Particularly striking was the pervasive influence of hegemonic masculinity throughout the YGBM's stories. The implications of these findings for future research and intervention development are discussed, as well as study strengths and limitations.